Metaanalisis Implementasi Landasan Ilmu Pendidikan dalam Pengembangan Modul pada Pembelajaran IPA dan Fisika - Nisak, Fitri; Septiani, Tri (Universitas Negeri Padang, 2019)
This research aims to analyze the implementation of educational foundations in developing modules on science and physics learning. The research method used is a survey with a sample of twenty articles in this case journal. Based on the results of the analysis of the article, obtained the implementation of the educational foundation of education in the development of effective modules in the learning of Science and Physiology. This effectiveness is seen from the level of education, learning materials and educational landscapes used in learning activities. The technical or cultural foundation is more effectively applied to the module compared to other standards. modules that are implemented with an educational foundation are more effective if applied at the high school level compared to the junior high school level. Judging from the Physics learning material, modules that are implemented with an educational foundation give a greater influence on wave material.